Cyclodextrin nanoparticles for diagnosis and potential cancer therapy: A systematic review - Karthic, Anandakrishnan; Roy, Arpita; Lakkakula, Jaya; Alghamdi, Saad; Shakoori, Afnan; Babalghith, Ahmad O.; Emran, Talha Bin; Sharma, Rohit; Lima, Clara Mariana Gonçalves; Kim, Bonglee; Park, Moon Nyeo; Safi, Sher Zaman; et al. (Frontiers in Cell and Developmental Biology, 2022)
Cancer is still one of the world’s deadliest health concern. As per latest statistics: lung, breast, liver, prostate and cervical cancers are reported topmost worldwide. Although chemotherapy is most widely used methodology to treat cancer, poor pharmacokietic parameters of anticancer drugs render them less effective. Novel nano-drug delivery systems has the caliber to improve the solubility and biocompatibility of various chemical compounds. In this regard cyclodextrins (CD), a group of natural nano-oligosaccharide possessing unique physicochemical characteristics has been highly exploited for drug delivery and other pharmaceutical purposes. Their cup-like structure and amphiphilic nature allows better accumulation of drugs, improved solubility and stability. Whereas its supramolecular chemical compatibility renders it highly receptive to various kinds of functionalization. Therefore combining physical, chemical and bio-engineering approaches at nanoscale to specifically target the tumour cells can help in maximizing the tumour damage without harming non-malignant cells. Numerous combinations of CD nanocomposites were developed over the years which employed photodynamic, photothermal therapy, chemotherapy and hyperthermia methods specifically against cancer cells. In this review we discuss the vivid roles of cyclodextrin nanocomposites developed for the treatment and theranostics of most important cancers to highlight its clinical significance and potential as a medical tool.